Limited enforceable international loans, international risk sharing and trade - Almuth Scholl (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
This paper analyzes the impact of limited enforceable international loans on international risk sharing and trade fluctuations in a two-country two-good endowment economy. Our specification of the punishment threat allows the exclusion from trade to last only finitely many periods and distinguishes between financial autarky and full autarky. Quantitative results show that limited enforceability substantially alters cross-country consumption correlations and the dynamics of net exports. In contrast to existing studies, risk sharing is low for large elasticities of substitution between the domestic and foreign goods. However, it remains challenging to explain the high volatility of the terms of trade empirically observed.
Keywords: E32; D52; F34; F41; 330